Vulnerability Assesment of Tourism Village Communities in The Special Region of Yogyakarta during The Covid-19 Pandemic - Shinta Permana Putri (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
This study aims to identify the vulnerabilities faced by tourist villages, especially the advanced tourist villages, during the Covid-19 pandemic. The research was conducted in five advanced tourist villages in different districts/municipalities in DIY. Basically, this study is a quantitative research. Data was collected through a questionnaire survey process among the village residents. The analysis technique used is descriptive statistics. The results of the study show that there are still several factors that remain vulnerable for the tourist villages' communities in DIY when facing Covid-19. These factors include financial conditions, the sustainability of tourism activities, the sustainability of social interactions, and the level of community adaptation. One way to reduce these vulnerabilities is through innovation. However, the vulnerabilities caused by Covid-19 are still greater compared to the efforts made by some other tourist villages. There are still several challenges faced by tourist villages for recovery, such as the lack of visitor enthusiasm, lack of innovation and attractiveness, lack of budget, and decreased visitor trust. In this regard, the preparedness and capacity of tourist village communities in facing disasters still need to be improved. Thus, efforts are still needed to prepare communities for possible future detrimental events and to enhance their capacity and resilience for recovery.